Poetic Encounter : Rhapsodies from the South - Aphane, Marota; Mtapuri, Oliver (Project Muse, 2018)
Poetic encounter: Rhapsodies from the South is compilation of poems by Southern African Writers from South Africa and Zimbabwe. The poems, were written not only to depict life but also tell tales of socio-political and economic history that Southern African people traversed from colonialism, apartheid to freedom. Therefore, readers from all walks-of-life can identify with themes such as apartheid, economic deprivation, religion and culture, love and so forth that are carefully ensconced in this compilation. The authors invite the readers, to not only indulge the lived injustice and violent nature of both our historic past and trajectory to the current state of affairs, but also appreciate, cry, smile and reminiscence about the life in general as encapsulated in this refreshing and aesthetic work of art -- the poetic encounter.